Anisotropic mechanical properties of extrusion-based 3D printed layered concrete - Liu, Chenkang; Yue, Songlin; Zhou, Cong; Sun, Honglei; Deng, Shuxin; Gao, Fei; Tan, Yizhong (Journal of materials science, 2021)
Extrusion-based 3D printed concrete is a promising material and processing technique for use in the construction industry. In this study, 3D printed specimens were loaded dynamically and statically to investigate their anisotropic characteristics. The experimental results showed that the average static compressive strength of the 3D printed concrete specimens was 115% of that of the cast specimens. Meanwhile, the dynamic compressive strength of DX specimens was significantly larger than that of other 3D printed specimens and cast specimens under the same impact pressure. In particular, ultrasonic pulse velocity values were used to quantitatively represent the anisotropy of 3D printed specimens. In conclusion, the anisotropic characteristics of 3D printed concrete were studied. The results indicate that the performance of 3D printed concrete was best (especially in the X -direction). The results provide a reference for engineers looking to design 3D printed components for use in construction.